Infiltration in the Principal Hadiths on the Surahs of the Qur'an : (An Analysis of Imam Al-Suyuti's Perspective) - Rengga Irfan; Khairul Bahri Nasution; Edriagus Saputra (International Journal of Research, 2026)
This study aims to analyze the infiltration of the ma’tsur sources, namely the hadiths about the virtues of the surahs of the Qur'an. Imam as-Suyūṭī in Tadrib ar-Rawi said that the hadiths concerning the virtues of the surahs of the Qur'an are mostly weak, only a few surahs are considered to be based on authentic hadiths, but in reality, other authentic or hasan hadiths were found in several other surahs, which he mentioned among others in the book al-Itqan fi 'Ulum Alqur’an. This study is a qualitative library research that is analyzed using content analysis techniques related to the infiltration of the hadiths about the virtues of the surahs of the Qur'an according to Imam as-Suyūṭī in his works al-Itqan fi 'Ulum Alqur’an and Tafsir ad-Dur al-Mantsur. While the secondary data sources of this study are books, articles, literature, journals and internet sites that are relevant to the research being conducted. The findings of this study are that some of the virtues of the surah mentioned have hadiths about its virtues with authentic and hasan hadiths, such as the virtues of Q.S. Hud, Q.S. al-'Ala, al-Bayyinah, as-Sajdah al-Mufashshal and others. However, there are also several hadiths of the virtues of surahs that are considered mawdhu and many are dha'if such as the virtues of surah al-Rahman, al-Isra' al-Musabbahat.